Northern Shrimp (Pandalus borealis) on Flemish Cap in July 1999 - Garabana, Dolores (Northwest Atlantic Fisheries Organization, 1999)
16 páginas, 5 figuras, 7 tablas.-- Scientific Council Meeting Results on shrimp from the EU survey on Flemish Cap in 1999 are presented and compared to those from previous surveys of the same series. The adult stock biomass (shrimp bigger than 20 mm of carapace length) remains high and only slightly bellow the 1998 maximum. It is dominated by age 5 shrimp. A comparative trial between the Lofoten gear, the one used in the survey, and a Campelen gear, indicates that the catch of large shrimp is 2.5 times bigger in the Campelen gear. This gear also catches large amounts of shrimp due to its smaller cod-end mesh size. The European Commission (DG XIV, Study 96-030) and CSIC supported this study. Peer reviewed